Environmental innovations, local networks and internationalization - Giulio Cainelli; Massimiliano Mazzanti; Sandro Montresor (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper investigates the drivers of the environmental innovations (EI) introduced by firms in local production systems (LPS). The role of firm network relationships, agglomeration economies and internationalization strategies is analysed for a sample of 555 firms in the Emilia-Romagna region, North-East of Italy. Cooperating with qualified local actors - i.e. universities and suppliers - is the most important driver of EI for most firms, along with their training policies and IT innovations. The role of agglomeration economies is less clear and seems to depend on the EI propensity of more locally oriented firms playing in district areas, which might even turn agglomeration into dis-economies. Networking effects and agglomeration economies are instead found to strongly promote the adoption of EI by multinational firms, thus highlighting the importance of local-global interactions. We provide some interesting findings for particular kinds of challenging EI in fields as CO2 abatement and ISO labelling, generally extending the analysis EI driver by joining local and international factors.
Keywords: C21; L60; O13; O30; Q20; Q58; F23; 330; Eco-Innovation; Foreign Ownership; Networking; District; Agglomeration Economics; Local Production Systems